DEVELOPMENT OF MATHEMATICS MODULE ON DATA COLLECTION MATERIAL FOR GRADE III AT SD IT NURUL ISHLAH BANDA ACEH - Nadhira, Dhiyaun; Yuhasriati, Yuhasriati; Safiah, Intan (Universitas Syiah Kuala, 2024)
This research aims to describe the stages, validity, practicality and effectiveness of the results of developing mathematics modules, as well as teacher and student responses to the use of mathematics modules as data collection material. This research uses research and development (RD) using the ADDIE model. The data source in this research was class III students, totaling 25 students. Data collection techniques were carried out using validation questionnaires and tests. Based on the research results, it is known that 1) Development of mathematics modules is an effective approach in learning data collection in elementary school classes; 2) The mathematics module developed in this research was proven to be effective in increasing students' understanding of data collection; 3) The use of mathematics modules in learning also provides flexibility for teachers in managing time and customizing material according to student needs; 4) The development of a mathematics module is deemed necessary, considering that educators and students only use student handbooks as the only teaching material. So it can be decided that there is effectiveness of the mathematics module in increasing understanding and mastery of data collection material for class III in elementary schools.